2012
DOI: 10.3766/jaaa.23.9.5
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Brainstem Responses to Level-Specific Chirps in Normal-Hearing Adults

Abstract: The study confirms the experimental hypothesis that at higher levels of stimulation the LS-Chirp generates significantly higher response amplitudes than both the CE-Chirp and the Click. It also generates a much better response resolution than the CE-Chirp, but the same response resolution as the Click.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
48
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 17 publications
6
48
1
2
Order By: Relevance
“…These findings are in agreement with Rodrigues and Lewis (2012) 24 who found that although chirp stimulation yielded larger wave V amplitudes at intensities < 60 dB, click was superior > 80 dB. Another study by Kristensen and Elberling (2012) 23 further support our findings. They reported that for all intensity levels tested, the amplitude of the ABRs to different chirp stimuli were significantly larger than click.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are in agreement with Rodrigues and Lewis (2012) 24 who found that although chirp stimulation yielded larger wave V amplitudes at intensities < 60 dB, click was superior > 80 dB. Another study by Kristensen and Elberling (2012) 23 further support our findings. They reported that for all intensity levels tested, the amplitude of the ABRs to different chirp stimuli were significantly larger than click.…”
Section: Discussionsupporting
confidence: 93%
“…Recently it was shown that indeed the LS-Chirp results in larger wave V amplitudes when compared to the traditional click stimulus. 23 Until commercially available however, click stimuli should remain standard when testing at neurodiagnostic levels.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in amplitude associated with the chirp stimulus are significant (p<0.001; n=18). These results are expected and similar to report in previous studies that compared chirp and click stimuli in the ABR recording [2,[4][5][6][7][8][9][10].…”
Section: Discussionsupporting
confidence: 80%
“…The first comprehensive description and mathematical formulation of the chirp was presented by Dau et al, 2000 [2] and since then several experiments have been carried out about its use within the auditory field in the international literature. In several publications it has been shown that an upward chirp is more efficient than a click when recording the auditory compound action potential, ACAP [3]; the ABR [4][5][6][7][8][9][10], and the auditory steady-state responses, ASSR (narrow-band chirps) [11][12][13][14]. Still, the chirp is a relatively novel stimulus and there is a need for more systematic studies (commercial accessibility in a medical device has less than 10 years).…”
Section: Introductionmentioning
confidence: 99%
“…The chirps (Kristensen & Elberling, 2012), which are brief sweep frequency stimuli, have been used in connection with both ABR and ASSR. The purpose of the chirp is to compensate for the delay from the basal to the apical part of the cochlea thus giving a simultaneous stimulation at all frequencies.…”
mentioning
confidence: 99%